Effects of acrylamide on mechanical and tribological properties of carbon fiber-reinforced epoxy composites. (May 2015) - Chong, Chuanguang; Shang, Wulin; Che, Yuanyuan; Huang, Jin; Zhou, Shaofeng; Zhang, Qiaoxin
The aim of this study was to clarify the effects of acrylamide on mechanical and tribological properties of short carbon fiber–reinforced bisphenol-A-type epoxy composites. The short carbon fiber/epoxy-based composites with or without acrylamide were prepared by solution blending and moderate temperature-curing techniques. Obviously, the short carbon fiber resulted in the enhancement of flexural strength and modulus of the short carbon fiber/epoxy-based composites in contrast to the epoxy-based composites. When the loading-level of short carbon fiber was 8 parts (corresponding to 100 parts of the epoxy matrix), the short carbon fiber 8/epoxy composites containing the same loading-level of acrylamide showed the highest flexural strength and modulus. At the same time, it was found that the addition of acrylamide further improved strength, modulus of the short carbon fiber/epoxy-based composites. Furthermore, the friction coefficient values of the acrylamide-modified short carbon fiber 8/epoxy composites were lower than that without the addition of acrylamide. The worn morphologies observed by scanning electron microscope revealed that the wear mechanism of the acrylamide-modified short carbon fiber 8/epoxy composites was fatigue wear.